Analgesic effects of gabapentin after scoliosis surgery in children: a randomized controlled trial. Issue 12 (17th September 2014) - Mayell, Antonia; Srinivasan, Ilavajady; Campbell, Fiona; Peliowski, Arie; Morton, Neil
Summary Background Postoperative pain remains an important challenge after scoliosis surgery in children. Opioids are the mainstay of treatment, and adult studies demonstrate gabapentin as a useful adjunct to opioids in the management of postoperative pain. Method Adolescent patients undergoing idiopathic scoliosis surgery were randomized to receive a single preoperative dose of gabapentin 600 mg or placebo. The primary outcome measure was total morphine consumption in mg·kg−1 between 0 and 24 h postoperatively. Secondary outcome measures included time to first rescue analgesia, pain intensity scores at rest and with movement, incidence of nausea, vomiting, pruritus, sedation, dizziness, presence of persisting pain symptoms, and patient satisfaction. Cumulative opioid consumption was calculated at each time point: 1, 4, 8, 12, 24, 48, and 72 h. Results The gabapentin group used 0.087 ± 0.06 mg·kg−1 of morphine at 1 h, 0.24 ± 0.12 mg·kg−1 at 4 h, 0.44 ± 0.17 mg·kg−1 at 8 h, and 1.29 ± 0.44 mg·kg−1 at 24 h. The placebo group used 0.121 ± 0.06 mg·kg−1 of morphine at 1 h, 0.35 ± 0.16 mg·kg−1 at 4 h, 0.56 ± 0.27 mg·kg−1 at 8 h, and 1.46 ± 0.68 mg·kg−1 at 24 h. There was no statistically significant reduction in opioid consumption in the patients receiving gabapentin. There were no significant differences in secondary outcomes. Conclusion A single preoperative dose of gabapentin did not show a significant difference in opioid consumption or pain scores in adolescents undergoing idiopathic scoliosis surgery. This study is the first pediatric randomized controlled trial to assess the effectiveness of a single dose of gabapentin on morphine consumption and analgesia following major surgery.